Measurement of Communication Performance Between 5G Devices in a 5G SA Network - Souto, Álef; Almeida, Lahis; Fonseca, Paulo; Meireles, Maria Alcimar Costa; Costa, Gledyson; Abreu, Sergio (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2024)
This work presents an end-to-end performance analysis of 5G devices connected to a private 5G Standalone (SA) network complied with Rel 15. The experiment was carry out in an indoor environment with two typical setups, using direct connection to the network core and wireless connection through 5G UEs. The metrics evaluated were: jitter, latency, throughput and the coverage parameters (SINR, RSRP and RSRQ). The results presented converged to a better performance in the setup with the server connected directly to the network core. In addition, the datasets containing the values of the collected parameters are made available for possible studies and reproduction of the results obtained.